Strategi Kepemimpinan, Motivasi Kerja dan Kompensasi terhadap Kepuasan Kerja serta Dampaknya pada Kinerja Karyawan Generasi Y PT. Bank BRI Wilayah I Jakarta - Novia Sarittama; Teuku Noerman (Sekolah Pascasarjana Perbanas Jakarta, 2017)
This study discusses the factors that affect the performance of generation Y employees for the purpose of proving variable menganalisasis and leadership, motivation, compensation and job satisfaction have an influence on employee performance generation Y. type eksplanaif research with survey method and the sampling technique using Snowball Sampling and Structural Equation Modeling analysis tools. The results showed that the variables of leadership, motivation, compensation and job satisfaction significantly influence employee performance generation Y. Based on these results the authors suggest that PT. Bank BRI Jakarta Regional I can maintain and improve the leadership, motivation, compensation and job satisfaction to improve employee performance generation Y.